The impact of ESG ratings on corporate value during COVID-19 pandemic: evidence from China and South Korea - Kim, Donghoon; Yoon, Sun-Joong (Seonmul yeongu (Online), 2024)
The COVID-19 pandemic has significantly disrupted global economies, posing unprecedented business challenges worldwide. This study examines the influence of Environmental, Social, and Governance (ESG) factors on corporate value in the context of the pandemic, focusing on China and South Korea. Using empirical analysis and data from Chinese A-share and South Korean KOSPI-listed companies, our research reveals complex dynamics. ESG had a negative impact on corporate value during the pandemic. However, firms with higher ESG scores demonstrated an insurance effect, mitigating risk. This effect held in both China and South Korea, highlighting the importance of ESG principles for resilience and sustainable growth in contemporary business practices. This research provides implications for ESG-focused businesses during crises.